2010
DOI: 10.1007/s00296-010-1488-0
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed electromagnetic fields decrease proinflammatory cytokine secretion (IL-1β and TNF-α) on human fibroblast-like cell culture

Abstract: The clinical use of pulsed electromagnetic fields (PEMF) in osteoarticular pathology is widely extended, although the mechanisms involved are unknown. The aim of this study was to evaluate the action of a new protocol of treatment with PEMF on liquid medium cultures of fibroblast-like cells derivates of mononuclear peripheral blood cells. Fibroblast-like cells growth was obtained in liquid medium culture from mononuclear cells (MNC) of human peripheral blood. The PEMF irradiation protocol included an intensity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 35 publications
2
27
0
Order By: Relevance
“…To our knowledge, very few studies have investigated the EMF effect on SFs and no data have been reported on human OASFs and the modulation of cytokine release (Murray et al, 1988; Marino et al, 2003; Varani et al, 2008; De Mattei et al, 2009). On the other hand, our data agree with previous studies showing that EMFs inhibit PGE 2 and cytokine production both in “in vitro” and in “in vivo” models, as well as in clinical studies (Lohmann et al, 2000; Chang et al, 2005; Benazzo et al, 2008a; De Mattei et al, 2009; Gomez‐Ochoa et al, 2010; Rohde et al, 2010). Here we show for the first time that EMFs significantly modulate the release of PGE 2 and both inflammatory and anti‐inflammatory cytokines in human OASFs, suggesting that cytokine production may be one of the most important functions affected by EMFs in these cells.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, very few studies have investigated the EMF effect on SFs and no data have been reported on human OASFs and the modulation of cytokine release (Murray et al, 1988; Marino et al, 2003; Varani et al, 2008; De Mattei et al, 2009). On the other hand, our data agree with previous studies showing that EMFs inhibit PGE 2 and cytokine production both in “in vitro” and in “in vivo” models, as well as in clinical studies (Lohmann et al, 2000; Chang et al, 2005; Benazzo et al, 2008a; De Mattei et al, 2009; Gomez‐Ochoa et al, 2010; Rohde et al, 2010). Here we show for the first time that EMFs significantly modulate the release of PGE 2 and both inflammatory and anti‐inflammatory cytokines in human OASFs, suggesting that cytokine production may be one of the most important functions affected by EMFs in these cells.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, several reports have evaluated the effects of extremely low‐frequency electromagnetic fields (EMFs) on tissue repair (Pesce et al ., ). In particular, the data support an anti‐inflammatory effect of EMFs by modulating cytokine profiles that drive the transition from a chronic pro‐inflammatory state of the healing process to an anti‐inflammatory state (Gomez‐Ochoa et al ., ). Molecular clarification of the mechanisms involved in the modulation of inflammatory factors following exposure to EMFs will provide a better understanding of the cellular responses induced by EMFs and provide a potential, additional treatment in non‐responding, chronic wounds (Lin et al , ).…”
Section: Introductionmentioning
confidence: 97%
“…These results are in accordance with early mediated reduction of NF-kB levels by EMFs described by Vianale et al on keratinocytes. Similarly, a recent study concluded that PEMF irradiation, not altering the cell immune-phenotype of the fibroblastlike cell population, provokes a decrease in the production of inflammatory-type cytokines (IL-1␤, TNF-␣) and an increase in cytokines of lymphocytic origin (IL-10) [119].…”
Section: Emfs/pemfs Cytokines and Wound Repairmentioning
confidence: 89%